Determination of Melting Layer Boundaries and Attenuation Evaluation in Equatorial Malaysia at Ku-Band - Abayomi Isiaka Yussuff; Nor Hisham Haji Khamis (Institute of Advanced Engineering and Science, 2014)
Upsurge in bandwidth demand in recent times for real-time data transmission have put serious constraints on satellite communication channels, leading to congestion of the lower frequency bands; necessitating migration to higher bands (Ku, Ka and V) with attendant problems such as signal fading, depolarization and attenuation due to presence of hydrometeors. There is need to separately account for attenuation due to the melting layer along the earth-space microwave links. One year data from ground-based S-band meteorological radar sourced from Kluang station of the Malaysian Meteorological Department was processed to build the vertical reflectivity of rain profile for UTM, Malaysia. Results from this work suggested that the effects of the melting layer on signal attenuation at Ku-band can be quite significant in the tropical and equatorial regions. It was estimated to be 13.36 dB and 15.44 dB at 0.01% of the time exceeded using Laws-parsons and Marshall-Palmer regression coefficients, respectively. Furthermore, it was observed that ITU-R. P.618-11 model largely under-estimated the attenuation along the slant-paths because of its failure to account for attenuation due to the melting layer in its formulation by its assumption of constant rain rate; thus rendering it unsuitable for rain attenuation predictions in the tropics.